Education, Work and Family Events in Women's Lives : Long-Term Developments and Recent Trends in East and West Germany - Blossfeld, Gwendolin Josephine (Budrich Academic Press, 2022)
This book investigates how educational expansion, the trend towards the service society and the German unification affect East and West German women's life courses and family lives. It focuses on educational enrolment, educational attainment level, labour force participation, career resources, social origin, the educational match among partners as well as historical periods and examines their consequences on women's entry into first motherhood as well as partnership formation and dissolution processes. Using longitudinal data from the National Educational Panel Study (NEPS), multivariate methods such as event history analysis were applied. The findings suggest that women's entry into motherhood during full-time education is highly dependent on women's age, social origin and the policy measures in a country.